2005
DOI: 10.1080/01926230500243045
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Axonal Degeneration in Mice with Deletion of Selenoprotein P

Abstract: Selenoprotein P is an abundant extracellular protein that is expressed in liver, brain, and other tissues. Studies in mice with the selenoprotein P gene deleted (Sepp-/- mice) have implicated the protein in maintaining brain selenium. Sepp-/- mice fed a normal or low selenium diet develop severe motor impairment and die, but Sepp-/- mice fed a high selenium diet remain clinically unimpaired. As an initial step to evaluate the effect of selenoprotein P deletion on central nervous system architecture, the brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 16 publications
1
34
1
Order By: Relevance
“…Normal function can be rescued with a diet supplemented with high levels of Se [24]. Although Se supplemented mice survive and appear normal, they exhibit severe brain stem axonal degeneration [30]. Recent evidence suggests SelP is transported into brain by the apolipoprotein E (ApoE) receptor, ApoER2.…”
Section: Discussionmentioning
confidence: 99%
“…Normal function can be rescued with a diet supplemented with high levels of Se [24]. Although Se supplemented mice survive and appear normal, they exhibit severe brain stem axonal degeneration [30]. Recent evidence suggests SelP is transported into brain by the apolipoprotein E (ApoE) receptor, ApoER2.…”
Section: Discussionmentioning
confidence: 99%
“…The latter are NADPH-dependent enzymes that convert oxidized thioredoxin back to the dithiol form. The plasma protein selenoprotein P is important in delivering selenium to the brain; mice lacking this protein die with severe degeneration of motor neurons unless their diet is enriched with selenium [34].…”
Section: Selenoprotein Pmentioning
confidence: 99%
“…Sepp1 delivers selenium to brain and testes through interaction with the apolipoprotein E receptor 2 (apoER2), and once in the cells, selenium is then incorporated into selenoproteins during their synthesis (Burk et al 2005; Burk et al 2009). Deletion of Sepp1 in mice decreases brain selenium levels and feeding these mice a selenium-deficient diet results in severe neurological impairments and death (Hill et al 2004; Valentine et al 2005; Valentine et al 2008). In our previous studies, we identified extensive axonal degeneration in the brainstem and thalamus of Sepp1 −/− mice fed a selenium-deficient diet for 14 days (Valentine et al 2008).…”
Section: Introductionmentioning
confidence: 99%